2015
DOI: 10.1007/s00381-015-2671-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the neurodevelopment of school-age children with and without single-suture craniosynostosis

Abstract: Sex differences in neurodevelopmental abilities among children with SSC are substantial, but not a unique correlate of this disorder as similar differences were observed among controls. Girls and those with sagittal synostosis have the lowest risk for academic problems. Boys with unicoronal synostosis warrant close developmental surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…For example, Fernald et al 16 found that by age 5 years the language skills of children from lower socioeconomic backgrounds were delayed by approximately 2 years in comparison with more socially advantaged peers. Similarly we have previously reported sex differences on the neurocognitive measures used in this test battery, 13 with males in both the case and control groups scoring lower than females from both groups on most measures. Thus, failing to adjust for sex, SES, and other demographic confounding variables may yield misleading results and variation across studies, depending on the population sampled.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…For example, Fernald et al 16 found that by age 5 years the language skills of children from lower socioeconomic backgrounds were delayed by approximately 2 years in comparison with more socially advantaged peers. Similarly we have previously reported sex differences on the neurocognitive measures used in this test battery, 13 with males in both the case and control groups scoring lower than females from both groups on most measures. Thus, failing to adjust for sex, SES, and other demographic confounding variables may yield misleading results and variation across studies, depending on the population sampled.…”
Section: Discussionsupporting
confidence: 80%
“…Given the mixed findings from previous studies, 4,6,9,12,13,15,23,34,41,48 the primary aim of this investigation was to determine whether school-age children with SSC, all of whom underwent cranioplasty, have deficits in language and memory skills in relation to demographically similar children without a craniofacial disorder. Use of a control group for such comparisons is critical but has been rarely undertaken in previous research on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental delays are generally mild and vary significantly, those with unicoronal or lambdoid synostosis being most vulnerable, whereas sagittal synostosis cases, the most common variety of synostosis, are spared. Boys with single-suture craniosynostosis score lower on academic and IQ tests than girls; and males are more likely than females to have learning problems (50 vs 30%); males with unicoronal synostosis have a 86% risk of learning disorder [ 2 ].…”
mentioning
confidence: 99%